Expression of Paxillin in Benign and Malignant Salivary Gland Tumors - Azadeh Andisheh-Tadbir; Aysuda Afshari; Mohammad Javad Ashraf (Shiraz University of Medical Sciences, 2019)
Statement of the Problem: Paxillin is a major cytoskeletal protein aberrantly deregulated in various human cancers and involved in tumor growth and invasion. However, the clinicopathological and prognostic significance of paxillin in salivary gland tumors (SGTs) is still unclear. Purpose: This study was conducted to evaluate the relationship between paxillin expression and clinicopathological features of patients with SGTs. Materials and Method: In this retrospective study, 50 paraffin-embedded tissue samples which were histologically confirmed as benign (pleomorphic adenoma, PA) or malignant (mucoepidermoid carcinoma (MEC), adenoid cystic carcinoma, ACC) SGTs, and 19 specimens from those with normal salivary gland (NSG) as a control group were assessed for paxillin expression using the immunohistochemistry. The paxillin expression in our samples was scored based on the extent and intensity of immunoreactivity and compared with histological type, clinical stage, and distant metastasis. Results: High paxillin expression was identified in 66% of SGTs whereas all patients with NSG showed low expression (p< 0.0001). Although the expression of paxillin in patients with benign and malignant tumors is similar, there is a significant difference between patients with PA, MEC, and ACC with that of the NSG (p< 0.0001). Paxillin expression was not correlated with clinicopathological features of patients Conclusion: High expression of paxillin was observed in tumoral tissues compared with the controls that establish an important role of paxillin in SGTs but its prognostic role was unclear and need further evaluation.